The Swedish inheritance and gift taxation, 1885-2004 - Gunnar Du Rietz; Magnus Henrekson; Daniel Waldenström (Uppsala University, Department of Economics, 2012)
This paper studies the evolution of the modern Swedish inheritance taxation from its introduction in 1885 to its abolishment in 2004. A thorough description is offered of the basic principles of the tax, including underlying ideas and ambitions, tax schedules, and rules concerning valuation of assets, liability matters and deduction opportunities. Using these rules, we calculate inheritance tax rates for the whole period for a number of differently endowed family firms and individuals. The overall trend in inheritance tax burden exhibits an inverse-U shape for all firms and individuals. Up until World War II, inheritance tax rates were very low (never above six percent), but in the postwar era tax rates increased rapidly for both inherited firms and individual fortunes. Effective tax rates peaked in the mid-1970s. Valuation reliefs were introduced in the 1970s, which sharply reduced tax rates for inherited family businesses. Tax rates for deceased individuals were first cut in 1987 and then significantly reduced in 1991 - 1992. Finally, inheritance and gift tax revenues were relatively small, around a quarter of a percent of GDP.
Keywords: H20; K34; D31; 330; Gift tax; Inheritance tax; Estate tax; Tax avoidance; Excess burden; Entrepreneurship; Ownership transfers of family firms; Erbschaftsteuer; Steuervermeidung; Excess Burden; Öffentliche Einnahmen; Familienunternehmen; Schweden